Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s11010-007-9415-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of castration on male rabbit lower urinary tract tissue enzymes

Abstract: Our data indicate that (1) significant differences exist in the activities of all three enzymes in the various organs associated with the lower urinary tract; and (2) that castration results in significant alterations in the activities of all three enzymes in the bladder body, base, urethra, and corpora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…At the molecular level, UB contraction is essentially dependant on the adenosine triphosphate (ATP) concentration in the bladder wall, as well as mitochondrial oxidative enzymes activity for energy production (Juan et al 2007). Castration decreases noticeably the activities of the mitochondria specific enzyme, citrate synthase of the UB muscle and mucosa (Juan et al 2007) which could be corrected by TRT. Nitric oxide (NO) is also one of the mediators of dilatation of the bladder neck and urethra (McVary 2006) by its smooth muscle relaxing effect in the urogenital system (Pradidarcheep 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, UB contraction is essentially dependant on the adenosine triphosphate (ATP) concentration in the bladder wall, as well as mitochondrial oxidative enzymes activity for energy production (Juan et al 2007). Castration decreases noticeably the activities of the mitochondria specific enzyme, citrate synthase of the UB muscle and mucosa (Juan et al 2007) which could be corrected by TRT. Nitric oxide (NO) is also one of the mediators of dilatation of the bladder neck and urethra (McVary 2006) by its smooth muscle relaxing effect in the urogenital system (Pradidarcheep 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that testosterone may influence the micturition reflex has been shown in several animal studies. Juan et al, (2007) reported that choline acetyltransferase activity, the indicator of cholinergic innervation, was significantly decreased in the bladder base and urethra 2 weeks after castration, indicative of the importance of testosterone in maintaining cholinergic nerve function. Lastly, testosterone increases angiotensin II levels and plays a role in the subsequent increase in contractility of vascular smooth muscles (Flynn et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The phasic response depends on the adenosine triphosphate (ATP) concentration in the bladder wall, whereas the tonic phase requires mitochondrial oxidative activity to generate energy. Castration of adult male rabbits resulted in a significant decrease in the activities of the mitochondria specific enzyme, citrate synthase of the bladder body and base, muscle and mucosa, urethra and corpora, while choline acetyl-transferse activity and calcium ATPase activity showed different responses depending on the sites (Juan et al, 2007). Preliminary evidence indicates that men with LUTS benefit from testosterone treatment, and pilot studies have also shown that testosterone therapy has a positive effect on LUTS in lateonset hypogonadism.…”
Section: Testosterone Deficiency Linked To Lutsmentioning
confidence: 97%
“…In the rabbit bladder outlet obstruction study, bladder dysfunction is mainly mediated by three cellular processes; 1) progressive denervation, 2) cellular mitochondria malfunction, 3) dysregulation of intracellular calcium storage and release from the sarcoplasmic reticulum (SR). Biomarkers for these three functions are calcium adenosine triphosphatase (ATPase) for calcium release, citrate synthase for mitochondrial function, and choline acetyl-transferse for cholinergic innervations (Juan et al, 2007). Bladder contraction can be divided into phasic and tonic period.…”
Section: Testosterone Deficiency Linked To Lutsmentioning
confidence: 99%